"I just do what others did." The role of descriptive norms in cyber bullying. - Chua, Jia Ying. (2010)
This study examined the effects of descriptive norms on cyber bullying behaviors. In the pilot study, participants were asked to rate the offensiveness of comments found online by the researcher and a list of 28 comments was thus derived. In the main study, undergraduate students (N = 44) were provided with descriptive information on whether cyber bullying was tolerated or not. Participants then chatted online with two anonymous individuals – “Interviewer” and “Interviewee”, and were instructed to choose comments the list derived in the pilot study in response to comments made by “Interviewee”. Results of this study did not show that descriptive norm on cyber bullying behaviors influence participants‟ subsequent 'flaming' behaviors. Possible explanations for the findings are discussed.